STATISTIK KRIMINAL TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA DI WILAYAH HUKUM PENGADILAN NEGERI JANTHO - Nurfah Nora Effendi; Ainal Hadi (Jurnal Ilmiah Mahasiswa Bidang Hukum Pidana, 2020)
Abstrak - Penulisan bertujuan untuk mengetahui dan menjelaskan tentang statistik kriminal tindak penyalahgunaan narkotika di wilayah hukum Pengadilan Negeri Jantho Aceh Besar. Penulisan menggunakan metode normatif dengan mengalisis putusan-putusan dan pasal-pasal yang berkaitan dengan penyalahgunaan narkotika. Dari pembahasan ini disimpulkan bahwa tindakan penyalahgunaan narkotika dapat dipidana jika seseorang terbukti menyimpan atau menggunakan narkotika tersebut dengan maksud untuk dirinya sendiri atau diperdagangkan untuk orang lain. Setiap tindakan yang menyalahgunakan narkotika dimuat dalam UU Nomor 35 tahun 2009 tentang narkotika dimana di dalam UU tersebut diatur hukuman untuk setiap tindakan penyalahgunaan narkotika. Hasil penelitian menunjukkan bahwa karakteristik dari pelaku penyalahgunaan narkotika lebih di dominasi oleh pelaku laki-laki yakni mencapai 455 orang sedangkan pelaku perempuan hanya 14 orang dalam rentang waktu 3 (tiga) tahun. Dan untuk kategori umur yang paling banyak melakukan tindakan penyalahgunaan narkotika adalah berusia sembilan belas tahun sampai empat puluh tahun (19-40). Rumusan pemidanaan dalam UU untuk tindak pidana penyalahgunaan narkotika dapat di jatuhi pidana yaitu pidana mati atau seumur hidup atau denda. Mengingat masalah penyalahgunaan narkotika sudah tidak asing di indonesia dan hukum dibuat untuk ditegakkan maka diharapkan kepada pemerintah dan aparat penegak hukum agar memberi sanksi tegas untuk menciptakan efek jera baik bagi pelaku penyimpanan, penyebaran maupun tindak pidana lainnya.Kata kunci : Tindak Pidana Penyalahgunaan Narkotika Abstract  - The criminal statistics are summary data in the form of recorded crime numbers based on specific times and places arranged to abridge understanding in drawing conclusions. Preparation of crime statistics can be used to overcome criminal acts intended to be able to find effective ways to prevent and overcome the crime. The Jantho Court has ruled four hundred thirty-eight (438) cases of narcotics abuse, but criminal statistics have not been prepared. The purpose of this study is to compile criminal statistics on narcotics abuse cases decided at the Jantho District Court which will explain the characteristics of the perpetrators, forms of narcotics abuse, and the types of sanctions given by the Jantho Court. The research method used is normative reseacrh by analyzing related articles and supported by reference books and other similar studies. The data source used is the decision of the Jantho Court regarding Narcotics Abuse from 2015-2017. All available data is taken and analyzed and then presented in table form. The results show that the characteristics of narcotics abuse perpetrators are dominated by male perpetrators, as many as 455, while women only fourteen perpetrators in 3 (three) years. The age category that mostly commits Narcotics Abuse is nineteen to forty years old (19-40). Moreover, the most types of work that commit criminal acts of narcotics abuse are entrepreneurial work, 130 respondents. The type of narcotics abuse carried out is « dealer/seller » as many as 65 people and « users » with a total of 151 people within three years. Sanctions given to perpetrators of narcotics abuse resolved in the Jantho Court are criminal sanctions in the form of imprisonment and criminal fines. It is suggested the the law enforcement officials compile rountinely criminal statistics and continue to pay attention and look at forms of crime, especially criminal acts of narcotics abuse in order to determine the prevention and handling of cases conclusively.